Pembinaan Moral dan Spiritual Remaja di Kampung Margamukti Melalui Kajian Kitab Lubab al-Hadits - Ahmad Fajar; Taufik Luthfi (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This dedication to: Youth Moral and Spiritual Development in Margamukti Village Through the Study of the Book of Lubab al-Hadith" is motivated by the main paradigm that knowledge of the Prophet's Morals can improve morally and spiritually for the reviewer. In this modern era, moral and spiritual qualities have experienced a lot of decline, various factors affecting it. Among them, the development of technology and information is a major factor in moral and spiritual decline, because teenagers who have new information through technology media cannot distinguish which ones are good and which are bad for their morals and spirituality. So that many of the youth in Margamukti Village spend their time on things that damage their morals and spirituality, it is considered important to direct the time and knowledge of the Youth in Margamukti Village to study the words of the Prophet in the book of Lubab al-Hadith. Thus, this service is expected to foster moral and spiritual youth in Margamukti Village and its surroundings. This research was conducted with a descriptive-qualitative method by explaining the Prophet's words scientifically and in depth. This research was systematically carried out by collecting data, analyzing data, and presenting the results of the analysis. The results of this service are expected to provide benefits to adolescents in the form of knowledge to return to maintaining moral and spiritual quality.